CLINICAL-HEMATOLOGICAL AND MOLECULAR-GENETIC FEATURES OF CHRONIC MYELOID LEUKEMIA - Sultonova Sherozakhon Xikmat qizi; Mohammad Din Asmo; Karimov Khamid Yakubovich; Boboyev Kodirjon Tuxtabayevich; Kazakbayeva Khamida Muhammadovna (Scholar Express Journals, 2021)
Molecular genetic studies have shown the need for an analysis for the presence of a quantitative determination of the chimeric oncogene BCR-ABL according to standardized methods to determine the effectiveness of the therapy used in patients with CML, and the need to determine the minimal residual disease (MRD) on the IS scale at 3, 6 and 9 months of treatment. The results of our studies indicate the effectiveness of imatinib therapy for CML, which is consistent with the results of international studies. The presence of a large molecular response in patients with CML to treatment with imatinib determines its high efficacy. Mutation analysis should be performed in patients who have never reached LMR, or when the BCR-ABL transcript level is more than 10-fold. If a patient loses LMR or shows an increase in the BCR-ABL transcript level, molecular testing should be performed every 1 to 3 months. Patients with partial and absent molecular response are indicated for therapy with the latest generation of TKI drugs or bone marrow transplantation.
Keywords: CML; LMR; PMR; CCR